Responding and adapting to change: an allied health perspective. Issue 4 (29th July 2020) - Beasley, Lisa; Grace, Sandra; Horstmanshof, Louise
Abstract : Purpose: The purpose of this paper is to review the literature on the response and adaption to change of allied health professionals. Understanding how individuals respond and adapt to change is essential to assist leaders to manage transformational change effectively. Contemporary health-care environments are characterised by frequent and rapid change, often with unrealistic and challenging time frames. Individuals operate independently, but also as members of teams, professions and organisations. Therefore, having a sound understanding of individual response to change is important for change leaders. In the Australian context, allied health professionals represent a quarter of the health-care workforce. There is a significant gap in understanding how allied health professionals respond and adapt to change. Design/methodology/approach: A scoping review was designed to report on the nature and extent of the literature on the response and adaption to change in the context of allied health professionals. Change leaders in the health-care environment face a number of complex challenges when attempting to facilitate change. While this scoping review did not identify any specific literature on the response and adaption to change of allied health professionals, it did however provide information on change models and factors to take into consideration when implementing a change process. Findings: The results of this scoping review identified findings in two main areas with regard to response and adaptation of allied health to change: a review of change management literature at the organisation level and change management for allied health. Most of the literature described organisational level change management without providing a structural framework for change. At the professional individual level, the literature focused on specific clinical interventions, rather than on the response and adaption to change for allied health. Minimal literature was identified in regard to the response and adaption to change of allied health professionals. In an environment characterised by continuous change and policy reform, a greater understanding of the response and adaption to change by allied health is a priority for research, policy and practice. Research limitations/implications: This scoping review was undertaken to explore the response and adaption to change of allied health. It sought to identify the factors that may explain why certain disciplines within the allied health professional group responded to change differently. Scoping reviews do not set out to comprehensively source all relevant literature but rather to ascertain the nature and extent of the published literature in the field. Therefore, it is possible that a systematic review might uncover additional relevant papers. However, this scoping review provides a clear indication of the nature and extent of the literature in allied health. Practical implications: Social implications: This scoping review will assist change leaders to gain a better understanding of theoretical frameworks of individual, team and organisational change processes and the impacts these have individually and collectively on change processes. Originality/value: To the best of the authors' knowledge, this scoping review is the first of its kind to identify the minimal literature available on the way allied health professionals respond and adapt to change.